A Review on the Faults of Electric Machines Used in Electric Ships. (5th March 2013) - Spyropoulos, Dionysios V.; Mitronikas, Epaminondas D.
Abstract : Electric propulsion systems are today widely applied in modern ships, including transport ships and warships. The ship of the future will be fully electric, and not only its propulsion system but also all the other services will depend on electric power. The robust and reliable operation of the ship's power system is essential. In this work, a review on the mechanical and electrical faults of electric machines that are used in electric ships is presented.